Effect of Infusion Duration of Pandan Leaves with Waste Cooking Oil in Soap Making Process - Rasyidi, Danial; Ibrahim, Ts. Dr. Aida binti Ibrahim (Progress in Engineering Application and Technology, 2023)
The aim of this study was to investigate the feasibility of using waste cooking oil as a resource for soap production through the infusion of pandan leaves. The infusion process was carried out for 2, 4, and 6 weeks using the cold process method, which is a simple and traditional technique that does not require specialized equipment. The process of synthesize of soap need cooking oil, lye (NaOH) and water as main materials. Parameter for making soap had been set such as type of soap making process, type of cooking oil and type of lye had been set up in this study. The study included the analysis of the oil’s color and viscosity. The colour of cooking oil brighter than waste cooking oil and infused waste cooking oil with pandan leaves and the viscosity of cooking oil slightly lower than waste cooking oil and infused waste cooking oil with pandan leaves. Next, other characteristics, as well as the visual observation of the soap’s appearance such as lye pocket, glycerine river and jellying were evaluated. The pH value, moisture content, foam stability, and foam height of the soap were also evaluated. The results showed that the pH values were similar to those of most commercial soaps, with values ranging from 9 to 10. The moisture content of soap made with infused waste cooking oil was slightly higher than that of soap made with waste cooking oil or cooking oil alone, due to the antioxidant-rich nature of pandan leaves and their high-water content. The foam stability of soap made with waste cooking oil was better than that of soap made with waste cooking oil or cooking oil alone, likely due to the foam-enhancing effects of pandan leaves, which contain high levels of saponin. Aim of this study is to synthsize soap using cold process by using infused waste cooking oil with pandan leaves. The effect of pandan leaves of infusion between pandan leaves and waste cooking oil duration time was investigated